Financial Conditions Indexes for the United States and Euro Area - Matheson, Troy (IMF Working Papers; Working Paper, 2011)
Financial conditions indexes are developed for the United States and euro area using a wide range of financial indicators and a dynamic factor model. The financial conditions indexes are shown to be useful for forecasting economic activity and have good revision properties.